Public Sector Reform and Service Delivery: A Catalyst for National Development in Nigeria - Chibuzo Charles Nwosu (Goodwood Publishing, 2026)
Purpose: This study explores the nexus between administrative restructuring, institutional efficiency, and the quality of public service delivery as key determinants of sustainable national progress. Drawing on the principles of New Public Management (NPM), this study examines how decentralization, transparency, accountability, and performance-based management influence the responsiveness and effectiveness of Nigeria’s public institutions. Methodology: A descriptive qualitative design was employed, utilizing documentary analysis to systematically review the literature, policy documents, and reform reports. Content and thematic analyses were used to interpret the findings. Results: The study argues that achieving meaningful national development requires reforms that not only streamline administrative processes but also strengthen human capital, technological innovation, and ethical standards in public administration. Conclusions: To achieve sustainable national development, Nigeria's public sector must transform into a citizen-centered, performance-driven, and digitally enabled institution. Limitations: This study addresses a critical gap by using the New Public Management theory to assess how managerial and accountability reforms impact the performance of service delivery. It explores institutional and governance barriers and offers policy recommendations aimed at strengthening Nigeria's public sector to ensure effective and sustainable service delivery. Contributions: This study makes significant contributions to the existing body of knowledge on public administration, governance, and development studies by providing novel insights into the interplay between public sector reforms, service delivery, and national development in Nigeria.